Komponen Utama dalam Instrumen Akreditasi Sekolah/Madrasah: Kajian tentang Mutu Guru dan Manajemen Sekolah/Madrasah - Zaskia; Hayatun Nufus; Husnul Yaqin; Hilmi Mizani (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to examine the main components of the madrasa accreditation instrument, particularly those related to teacher quality and school management. The research employed a literature study approach by collecting data from various sources, including books, scientific journals, official regulations, and previous studies relevant to educational accreditation. The collected data were analyzed descriptively through review and interpretation processes to develop a comprehensive understanding of the role of teacher quality and school management in improving the quality of madrasa education. The findings indicate that accreditation serves as an important instrument for educational quality assurance because it evaluates various aspects of educational implementation comprehensively. Teacher quality is considered a key indicator, covering academic qualifications, teaching performance, and professional development. Meanwhile, school management includes aspects such as planning, leadership, human resource management, evaluation, and school culture. These two aspects are closely interconnected, as effective school management can support the improvement of teacher professionalism and the quality of learning. Therefore, continuous improvement in teacher quality and the strengthening of school management are essential factors in supporting successful accreditation and enhancing the overall quality of madrasa education.